OPTIMALISASI KETEPATAN PEMBERIAN OBAT DENGAN PENERAPAN PROSEDUR DAN KOMUNIKASI SBAR DALAM PELAKSANAAN CLINICAL HANDOVER PERAWAT DI INSTALASI RAWAT INAP RSUD KOTA DEPOK PERIODE JULI 2019 - Fakhri Mubarok (2019)
To improve safe medication management, nurses should implement the '12 rights' principle in every step of medication administration. The quality of transferred patient medication information can be affected by the conformity of procedural pathways that focused on patient-centered care and the standardized effective communication technique application in shift-to-shift nursing clinical handovers so it can impact on transfer of information more accurately, efficiently, and consistently so that medication administration accuracy will be optimally accomplished. This study aims to determine the correlation between the procedures and SBAR communication implementation in clinical handovers with medication administration accuracy. It was an observational analytic approach with cross-sectional design. The subjects of this study were 40 nurse respondents. The univariate analysis showed 85% of clinical handover procedure implementation within good category, 60% of SBAR communication application within very good category, and 87.5% of medication administration accuracy within good category. The results of Fisher's test showed there are correlation between the clinical handover procedures implementation to medication administration accuracy with P-value 0,000 and correlation between the SBAR communication application to medication administration accuracy with P-value 0.001. In conclusion, there are correlation between the procedures implementation and SBAR communication application in nursing clinical handovers with medication administration accuracy.